CO2 flux measurement in four different ecosystems - TAUFAROVÁ, Klára; HAVRÁNKOVÁ, Kateřina; CZERNÝ, Radek; JANOUŠ, Dalibor (Contributions to Geophysics and Geodesy, 2021)
The ability of four different ecosystems (Norway spruce forest, mountain grassland, wetland and cropland) to bind the atmospheric carbon was estimated using eddy covariance technique. Net ecosystem production resulted from the potential of ecosystems to bind carbon and from their specific growth conditions. The growing season of the spruce forest is the longest in comparison to the other ecosystems, which results in its high productivity potential. Its activity starts early in the spring, when the soil is still covered with snow and the buds do not germinate yet. The growing season of mountain grassland is restricted to the snow cover. Right after the snow melt (late spring), the production starts to grow rapidly. The production period is relatively short, in the late summer carbon losses already prevail over assimilation. The wetland production is distributed relatively uniformly throughout the vegetation season. Carbon losses are significantly enhanced by methane efflux. Evaluation of carbon losses gives 98% GPP (CO2 and CH4) or 74% GPP (CO2 only). The shape of the cropland site production course is similar to the grassland, however its total respiration losses are smaller (73% at cropland in comparison to 99.5% at grassland). The harvest is a specific feature of the cropland – the grown biomass is taken away in the late summer and the carbon thus bounded is released during food chain utilisation, combusting, and decay.